Comparison between superpave gyratory and Marshall laboratory compaction methods - Aziz Memon, Naeem (2006)
The last decade has witnessed a dramatic increase in vehicular traffic on roads in developing countries like Malaysia. This has raised additional traffic, augmented axle loads and increased tire pressure on pavements designed for earlier era. In this regard, besides considering increasing the pavement thickness due to the traffic loads, steps must also be taken to extend the pavement life by using different compaction methods such as gyratory laboratory compaction method to have durable mix and better simulate field conditions. However, the main shortcoming of gyratory compaction method is that the gyratory compactor is very costly as seven times more than that of the available Marshall hammer.To overcome that shortcoming, studies have been done to compare both laboratory compaction methods but more are needed to verify different findings according to different conditions and climate. In this research four asphalt concrete mixes asphalt wearing course(ACW)10, ACW14, ACW20 and ACB28 were designed using Marshall mix design to evaluate HMA properties such as density and air voids. Based on the Marshall results, specimens were fabricated to obtain the required number of gyrations that could produce same results in terms of density. Using the equivalent number of gyrations samples were designed using superpave to obtain the optimum bitumen content (OBC). The results indicate that at 75 blows Marshall, the equivalent number of gyrations for ACW10, ACW14, ACW20 and ACB28 are 105, 67, 58 and 107 respectively. The results also suggest that there is no significant difference in OBC except for ACW10, which is 0.6%. This shows that numbers of gyrations obtained are reasonable in comparing with 75 blows Marshall.